Causes and Effects of Water Consumption Drop by the Population of Cities in Poland - Selected Aspects - Gorączko Marcin; Pasela Rafał (Bulletin of Geography. Socio-Economic Series, 2015)
The article presents, with an example of four cities of various size, a phenomenon of a drop in water consumption by the city population in Poland. The paper draws on 1995-2012 official statistics. A significant decrease in household water consumption was observed, which refers to both the total water volume used by households as well as the average daily water consumption per resident. The article also determines the most essential factors affecting the amount of water consumed, out of which the price of water appears to be of the most significant one.